Visualization techniques of grease fluidity - Sakai, Kazumi (Frontiers in Mechanical Engineering, 2024)
Energy-saving technology has become increasingly significant as one of the carbon-neutral options for suppressing recent global warming. Grease-lubricated bearings have been used in various automotive and industrial machinery, requiring low torque and long service life for energy-saving performance, which is greatly influenced by grease fluidity. A numerical approach for understanding grease fluidity is very complex since grease is a non-Newtonian fluid with thixotropic properties. Visualization technique is one of the helpful methods to understand the complex grease fluidity and apply it to practical use. This paper describes state-of-the-art visualization techniques, such as fluorescence method, particle imaging velocimetry, infrared spectroscopy, X-rays, and neutron beams.